Paciente de sexo femenino de 52 años de edad con artritis reumatoide - Montesdeoca Herrera, Sergio Antonio (2018)
Rheumatoid arthritis is a disease that causes pain, swelling and stiffness in the joints or joints. This disease often occurs in more than one joint and can affect any joint in the body. People with this disease may feel sick and tired, and sometimes they may have a fever. Anyone can get this disease, although it occurs more often in women and in older people. The most important feature of the disease is polyarthritis or symmetric synovitis that typically affects the hands, wrists and feet initially and can later affect any synovial joint such as knees, ankles, elbows and shoulders. Prevalence studies are a very important tool when studying this disease, because they form the first step to estimate the social and economic burden of this and allow comparison with other ailments, finding, through this method, a guide for the decision making in public health and better targeting of resources. Knowing the factors that influence the development of the disease and its symptomatology, can help people to know how to prevent their progression and thus avoid the destruction of the joints. Pharmacological therapy is the best solution to reduce the symptoms of the disease although combining it with moderate exercises could achieve better results, since the articular rigidity characteristic of this disease decrease with the movement of the joints. A healthy diet also helps the disease does not cause more damage because obese people can suffer damage to the joints of the knees affected by the weight load they would support. With the results obtained after providing the appropriate treatment, it was concluded that if the disease is diagnosed in time, a favorable therapeutic response can be achieved and thus improve the quality of life of people suffering from rheumatoid arthritis.